2019
DOI: 10.1001/jamanetworkopen.2019.6762
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cancer Among Children and Young Adults With Congenital Heart Disease Compared With Healthy Controls

Abstract: IMPORTANCEAdult patients with congenital heart disease (CHD) have an increased incidence of cancer, presumably owing to repeated radiation exposure, genetic predisposition, or repeated stress factors during heart interventions. However, there are limited data on the risk of cancer in children and young adults with CHD compared with the general population. OBJECTIVE To determine the risk of developing cancer from birth to age 41 years among patients with CHD compared with healthy matched controls. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 26 publications
6
49
2
Order By: Relevance
“…A recently published study from the Swedish Patient Register showed an overall hazard ratio for cancer of 2.24 in patients with congenital heart disease compared with healthy controls. An even higher hazard ratio of 3.37 is reported in patients born from 1990 to 1993, which fits well to our study group [34]. This study claims that radiation dose from cardiac catherization might not be the only contributor to increased risk of cancer in patients with congenital heart disease.…”
Section: Discussionsupporting
confidence: 90%
“…A recently published study from the Swedish Patient Register showed an overall hazard ratio for cancer of 2.24 in patients with congenital heart disease compared with healthy controls. An even higher hazard ratio of 3.37 is reported in patients born from 1990 to 1993, which fits well to our study group [34]. This study claims that radiation dose from cardiac catherization might not be the only contributor to increased risk of cancer in patients with congenital heart disease.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to testicular cancer, our study provided evidence for other associations between birth defects and cancer diagnosed in adulthood. For example, the odds ratio for congenital heart defects and overall cancer was 1.28 (1.02 to 1.59), similar to or lower than those previously suggested for adults 143536. Another example was nervous system defects, with a 15-fold increased risk of cancer before the age of 5, whereas the odds ratio for adults was reduced to 1.76 (1.16 to 2.65).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have reported declining risk of cancer with age, but most were limited by size, shorter follow-up time, or both, and few were able to assess specific birth defects 89101112133536. Only three studies included adults, and these evaluated only nervous and circulatory system defects and congenital heart defects 143536. In our study, we found that although the increase in overall cancer risk declined with age, it persisted into adulthood for both non-chromosomal and chromosomal anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several epidemiologic studies associated with childhood congenital malformations with cancer risk. In a recent study from the Swedish Patient Register, e.g., Mandalenakis et al 26 showed that C-AYA patients with any kind of CHD had increased risk of developing cancer (hazard ratio = 2.24, 95% CI, 2.01-2.48) compared to their matched controls, from Total Population Register in Sweden, who did not have CHD (2% vs. 0.9%). Here, we also showed that 67 (4.4%) of our C-AYA patients with solid tumors carried at least one germline P/LP variant in a CHD-related gene (7 KCPG and 19 candidate genes) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%